The Effect of Concentration and Soaking Time on The Shallots Exract Against The Growth of Stem Cuttings Dersono Guava (Syzigium Malaccense) - Al Ibrahim, Tegar Bara; Qomariah, Umi Kulsum Nur; Nasirudin, Mohamad (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The purpose of the research to determine the effect of shallot extract concentration and soaking duration on the growth of stem cuttings of water apple (Syzygium malaccense), observed through shoot number, leaf number, and shoot emergence time over four weeks. A 4 × 3 factorial randomized block design with five replications was applied. The results showed that the combination of shallot extract treatments had a highly significant effect on all variables. The best outcome was obtained from the 80% concentration with 4-hour soaking (K2L2), which produced the highest average number of shoots (11.8), leaves (16.6), and the fastest shoot emergence (0.4–0.6 weeks). In contrast, excessively high concentrations (100%) tended to inhibit growth, likely due to phytotoxic effects. Natural auxins and cytokinins in shallot extract played an important role in stimulating cell division and vegetative growth. These findings indicate that shallot extract can be used as an effective natural alternative to synthetic growth regulators for vegetative plant propagation. Keywords: Stem cuttings, shallot extract, Syzygium malaccense.